2020
DOI: 10.1017/s0033291720000136
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking as a risk factor for schizophrenia or all non-affective psychoses

Abstract: Background Smoking tobacco is regarded as an epiphenomenon in patients with schizophrenia when it may be causal. We aimed to examine whether smoking status is related to the onset of schizophrenia or the broader diagnosis of non-affective psychosis, including schizophrenia. Methods We used data from The Health Improvement Network primary care database to identify people aged 15–24 between 1 January 2004 and 31 December 2009. We followed them until the earliest of: first diagnosis of schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Compared with adults without psychosis, those with psychosis had a 1.5- to 1.6-times higher adjusted prevalence of past-month any tobacco use and past-month cigarette smoking overall; had a 1.2- to 2.0-times higher prevalence within almost every age, sex, and racial and ethnic group; and had a higher adjusted prevalence of e-cigarette use and any other tobacco product use overall and in most subgroups. A recently proposed bidirectional association that suggested smoking may be causally associated with an elevated risk of psychosis through shared genetic liability to smoking and psychosis 33 , 34 may help explain the present study’s findings. Moreover, people with psychosis may seek nicotine to alleviate the symptoms of their illness or the adverse effects of antipsychotic medications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Compared with adults without psychosis, those with psychosis had a 1.5- to 1.6-times higher adjusted prevalence of past-month any tobacco use and past-month cigarette smoking overall; had a 1.2- to 2.0-times higher prevalence within almost every age, sex, and racial and ethnic group; and had a higher adjusted prevalence of e-cigarette use and any other tobacco product use overall and in most subgroups. A recently proposed bidirectional association that suggested smoking may be causally associated with an elevated risk of psychosis through shared genetic liability to smoking and psychosis 33 , 34 may help explain the present study’s findings. Moreover, people with psychosis may seek nicotine to alleviate the symptoms of their illness or the adverse effects of antipsychotic medications.…”
Section: Discussionsupporting
confidence: 66%
“…Tobacco Use, Nicotine Dependence, and Cessation Methods in Adults With Psychosis most subgroups. A recently proposed bidirectional association that suggested smoking may be causally associated with an elevated risk of psychosis through shared genetic liability to smoking and psychosis 33,34 may help explain the present study's findings. Moreover, people with psychosis may seek nicotine to alleviate the symptoms of their illness or the adverse effects of antipsychotic medications.…”
Section: Jama Network Open | Substance Use and Addictionsupporting
confidence: 65%
“…Tobacco as well could take part in psychosis risk [13,15,24,62] with a 2-fold increase in risk of schizophrenia or other schizophrenia spectrum disorders and a dose-response mechanism [63]. The mechanism underlying this association is not clear, with some hypotheses in favor of an rGE correlation where a genetic arrangement that favors the development of primary psychosis also favors tobacco smoking for attenuating a specific distress that manifests in the prodromal phase of the disorder.…”
Section: Adolescence-related Environmental Risk Factorsmentioning
confidence: 99%
“…Many previous studies have confirmed the association between cigarette smoking and neurodegeneration ( Deochand et al, 2016 ; Yu et al, 2016 ; Liu et al, 2020 ), cognition and memory ( Ge et al, 2019 ; Wei et al, 2020 ; Martin Rios et al, 2021 ), and mental disorders, such as attentional deficits ( Joo et al, 2017 ; Lawrence et al, 2021 ) and schizophrenia ( Donde et al, 2020 ; King et al, 2020 ), considering the wide distribution of nicotinic acetylcholine receptors (nAChRs) throughout the brain ( Levin et al, 2015 ). Based on the fact that nicotine is one of the main addictive components of an e-cigarette, there is increasing recognition that e-cigarettes impact brain functions, for instance, e-cigarettes impaired the integrity of the blood-brain barrier (BBB) and exacerbated the cognitive dysfunction ( Chen et al, 2021 ), mental disorders ( Pham et al, 2020 ), vascular inflammation ( Kaisar et al, 2017 ), metabolic imbalance ( Debarba et al, 2020 ), and neurotoxicity ( Ruszkiewicz et al, 2020 ) in the brain of human and animal models, while the effects of ENDS with specific flavor on the behaviors need further disclosure.…”
Section: Introductionmentioning
confidence: 91%